2014
DOI: 10.1016/j.spinee.2013.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in a chronic musculoskeletal pain with disability population is independent of pain and depression

Abstract: BACKGROUND CONTEXT Insomnia is frequently experienced by patients suffering from chronic musculoskeletal disorders, but is often seen as simply a symptom of pain or depression, and not as an independent disorder. Compared to those who experience only chronic pain, patients with both chronic pain and insomnia report higher pain intensity, more depressive symptoms, and greater distress. However, insomnia has not yet been systematically studied in a chronic musculoskeletal pain with disability population. PURPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 36 publications
(48 reference statements)
3
34
0
4
Order By: Relevance
“…Current findings nonetheless confirm the previously documented associations of sleep with pain (7,13,17,20,39,40) and depression (20,37,38). In our sample, however, depressive symptoms entirely accounted for the association of sleep with pain; nor was there any association of baseline sleep disturbance with one-year change in pain.…”
Section: Discussionsupporting
confidence: 89%
“…Current findings nonetheless confirm the previously documented associations of sleep with pain (7,13,17,20,39,40) and depression (20,37,38). In our sample, however, depressive symptoms entirely accounted for the association of sleep with pain; nor was there any association of baseline sleep disturbance with one-year change in pain.…”
Section: Discussionsupporting
confidence: 89%
“…[28][29][30] Using the insomnia severity index (ISI), 31 , 32 a previous study by our group found that 94.5% of patients with CDOMDs entering an FRP reported a clinically signifi cant level of insomnia symptoms, and 70% reported moderate to severe symptoms. 33 Furthermore, insomnia was found to be independent of pain and depression, suggesting that insomnia was a comorbid, rather than a secondary symptom in this CDOMD population. Because of the "stand alone" characteristic of insomnia in CDOMDs, it is hypothesized that insomnia is an independent predictor of socioeconomic and health-related outcomes after an FRP, particularly because insomnia has been found to be a signifi cant predictor of work-and health-related outcomes in general working populations.…”
mentioning
confidence: 76%
“…When faced with chronic pain and disability, many patients exhibit depressive symptoms, so depressive symptoms were assessed with the Beck Depression Inventory (BDI), scored from 0 to 63 . Many chronic pain patients also suffer from insomnia, which can occur independently of pain and depression, so insomnia was assessed with the Insomnia Severity Index (ISI), scored from 0 to 28…”
Section: Methodsmentioning
confidence: 99%